[Linking ICF codes to clinical real-life assessments: the challenge of the transition from theory to practice] (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
According to the latest WHO guidelines, the ICD-ICF joint use currently represents the most agreed method to portray a patient’s Care Pathway during a hospitalization. On this note, ICS Maugeri carried out an internal project aiming to identify the ICF codes that better describe the rehabilitation pathways in its Italian Institutes. 2 main goals so far have been achieved: 1. To re-conceptualize the Care Pathways thought the lenses of the ICD-ICF frameworks; 2. To link, whenever possible and by means of the WHO-ICF linking rules, each pertinent ICF code to the most appropriate assessment method, harmonizing its outputs to the 0-4 ICF Likert scale. The current project represents a first attempt towards the creation of a standard functioning assessment methodology to be implemented in rehabilitation settings. Despite being referred to the Maugeri group only, the ICD-ICF procedure described could hopefully be extended to other settings, representing a support for health information technologies.